(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: The main focus of the study was the development of a Photovoltaic System Trainer. It was designed and constructed as an instructional device to provide students with a more engaging and experiential learning of the photovoltaic system. This study utilized developmental and descriptive methods of research. For developmental method, processes were used like planning, designing, lay-outing, constructing, assembling, pre-testing and revising, final product testing and evaluating. While the descriptive method was evaluated in terms of product quality in performance efficiency, durability, reliability, maintainability, and conformance; and for the acceptability like design, functional suitability, security, usability, and portability were also evaluated. A research-made instrument was formulated and administered to twenty-five experts for quality product evaluation and seventy-five respondents for its acceptability. The result showed that the trainer has a dual-powered device, interactive learning, and can extend battery operation as its technical features can reinforce the teaching and learning processes; for quality evaluation, the overall results showed in terms of performance efficiency, durability, reliability, maintainability, and conformance were very good. Further, for acceptability evaluation, the overall results in terms of design, functional suitability, security, usability, and portability were very highly acceptable. The users manual was developed to guide the users on the product specifications, features, parts and functions, operating procedures, maintenance, dos and don’ts, and troubleshooting guide. The activity sheets were beneficial to both students and teachers in learning processes. Finally, the trainer is ideal for the BSIT Electronics/Electrical and BTLED Industrial Arts curriculum and conducting the National Competency Assessment by TESDA.